(3GdGJLGgGJ GdMOjKI aj GdGOGQI h JMOjGJ GdeOjQjf (B/s - (3HQHQ, cGeds ((3HjQhJ(B: s (3OGQ Gdefgd GddHfGfj(B, s, 2010)
(3JWhQ GdacQ GdGOGQj GdMOjK (B: (3GdeOQSI GdcdGSjcjI , GdSdhcjI h GdeOGQS GdMOjKI , GdCSS GdMOjKI dYe GdGOGQI , GdeMjWGJ h GJNGP GdbQGQGJ GdJNWjWjI , GdJfXje GdGOGQj h MQcjGJg h GdJhLjY GdGOGQj h CNjQG GdQbGHI GdGOGQjI(B.s
(3agQS GdfeGPL h GdGTcGd h GdLOGhd U(B.341s
Keywords: (3GdEOGQIs